(untitled) (BioMedical Research in Medicine (BMR Medicine) (ISSN 2349-0756), 2024)
Tuberculosis is a major public health problem globally and there is a relative paucity of data on the clinical course of TB in immunosupressed adolescents. We report a case of cavitatory pulmonary tuberculosis in a diabetic adolescent. Although cavitatory lung lesions being not so common in pediatric age group. Co-existense of Diabetes Mellitus and Tuberculosis emphasizes the need for intensive screening for tuberculosis in Type 1 DM children.